Electrical distribution system efficiency and effectiveness with simple mathematics at the Indonesian aviation Polytechnic of Curug - Yenni Arnas; Zulina Kurniawati; KGS M. Ismail (International Journal of Trends in Mathematics Education Research, 2022)
Indonesian Aviation Polytechnic of Curug (PPI Curug) uses power from PLN of 3 Mega Watts. Since the beginning implementation of the electrical system at the PPI Curug Campus, adjustments have never been made. The additions of a new distribution system did not go through careful planning, this can be shown by the data that until now there are still buildings at PPI Curug which are supplied with a voltage of 110 V per phase. Upgrading the electrical system in several buildings that are supplied with a voltage of 110 V per phase has been carried out slowly through the adjustment mechanism of the electrical installation in these buildings, and has not yet touched on the distribution system. The large number of power transformers turned out to be not proportional to the power supply borne by each transformer, and overall none of the transformers was burdened more than 40% of the nominal load. On the other hand, the number of electricity subscription bills paid by PPI Curug has increased from year to year. This study aims to determine whether the electricity distribution system used at PPI Curug is currently effective and efficient and to determine an effective and efficient electricity distribution system based on the characteristics of the area and type of load at PPI Curug. The research method used is an evaluative qualitative method which will describe the condition of the distribution system and installation at PPI Curug, then evaluate it based on existing standards. The differences that exist between the real conditions in the field and the existing standards will be used as conclusions and suggestions for improvements. The results showed that the percentage value of the efficiency of all transformers showed a value of 95% so that the efficiency of the transformer at PPI Curug was categorized as good, but the condition that there was still a large amount of unused power needed to anticipate the use of electrical power beyond the requirement.